Mechanical interaction of the egg parasitoid Anastatus bifasciatus (Hymenoptera: Eupelmidae) with artificial substrates and its host egg - Rebora, Manuela; Salerno, Gianandrea; Piersanti, Silvana; Saitta, Valerio; Gorb, Elena; Gorb, Stanislav N. (Frontiers in Mechanical Engineering, 2022)
Egg parasitoids play an important role in biological control of pest species attacking and killing their hosts at an early stage of their development. During the antagonistic coevolution with their hosts, egg parasitoids have developed a great ability to locate their host using chemical cues. A considerable amount of literature is available on this topic, while nothing is known about a possible adaptation of egg parasitoids to topography and mechanical properties of egg surface features and its shape when attaching to the host egg for oviposition. In the present investigation, the attachment ability of adults of both sexes of the egg parasitoid Anastatus bifasciatus (Hymenoptera: Eupelmidae) to artificial (polishing paper, flat glass, glass beads as dummies of the host egg) and natural surfaces (eggs of Halyomorpha halys and Nezara viridula (both Heteroptera: Pentatomidae), with different roughness and wettability, was measured using centrifugal force tester and traction force experiments. The parasitoid attachment devices and the egg surfaces were examined under cryo scanning electron microscope, wettability and roughness of natural and artificial substrates were characterised. We detected differences in the attachment devices and attachment ability of the two sexes. The collected data revealed a special ability of the female to attach to the eggs of the host species, thus suggesting an adaptation of the A. bifasciatus female to the surface features of the eggs during oviposition.